Genetic variation and trait relationship in the exotic and local eggplant germplasm (Bangladesh Journal of Agricultural Research, 2010)
Sixteen genotypes of local and exotic germplasms were studied to estimate variability, hcritability, genetic advance, and correlation coefficients. High genotypic and phenotypic coefficients of variation were obtained for number of fruits/plant, individual fruit weight, and yield per plant. Heritability and genetic advance were also high for these traits indicating the possibility of selection to improve these characters. Yield of fruits showed highly significant and positive association with number of fruits per plant and individual fruit weight, which indicate the importance of these characters during selection for high yielding genotypes in eggplant. Among the genotypes, Islampuri produced the highest fruit yield (58.8 t/ha) followed by Tall begun (52.8 t/ha) and EG 120 (49.6 t/ha). Incidence of borer infestation ranged from 3.0 to 20.6 %. The lowest borer infestation was found in EG 120 (3.0%), while it was the highest in EG 192 (20.6%) Key Words: Genetic variation; trait relationship; exotic and local germplasm; eggplant. DOI: 10.3329/bjar.v34i1.5758Bangladesh J. Agril. Res. 34(1) : 91-96, March 2009